THE ASSESMENT OF SIGNIFICANCE OF THE RETROPERITONEAL LYMPH NODE DISSECTION IN PROXIMITY OF METASTATIC TUMOR WITH MAIN VESSELS IN PATIENTS WITH GERM CELL TESTICULAR TUMORS - O. S. Tereshin; S. P. Zotov; A. V. Vazhenin; A. O. Mamonova (Вестник хирургии имени И.И. Грекова)
The therapeutic approach should be defined more exactly in proximity of residual retroperitoneal metastases of germ cell testicular tumor and main vessels (left after chemotherapy). The data of 29 (24%) patients were analyzed over a period of time since 2003 till 2011. The general survival was 82% in the group without lymph node dissection (17 patients) in median observation of 27.5 months. The proximity with main vessels was registered in half of the cases in the group of operated patients (12 people), a single vascular reconstruction was required. The general survival was 97% in median observation for 35 months. The involvement of main vessels of retroperitoneal space significantly complicated the retroperitoneal lymph node dissection, but didn’t have negative prognostic value.